Error Analysis of Form for English Compositions - Nehru P. Pongsapan (LPPM UKI Toraja, 2012)
Error analysis is an invaluable source of information to teachers. It provides information on students' errors which in turn helps teachers to correct students' errors and also improves the effectiveness of their teaching. The study of errors by themselves would have been misleading; the study of errors in contrast to the number of correct responses gives a good picture of which items are being mastered and which are not. Therefore, this study hopes to enlighten teachers on the errors that require remedial work so that time is not wasted on teaching grammar items which pose little or no problems to the majority of the students in relation to writing compositions. The main purpose of this study is to categorize and evaluate the types of errors that students make in written compositions. This study, therefore, does not set out to investigate the factors that contribute to the students' errors. Although an investigation of the contributing factors may seem related to this study, it is deemed that such an investigation would require a separate study as it is a large field to be dealt together with this report. The present study also shows that there is a difference in the percentage of errors for the items studied between the rural and urban students. Rural students had a higher percentage of errors in most of the areas except for simple future tense and pronouns. As for subject-verb agreement both the rural and the urban students had the same percentage of errors (6%). Rural students have serious problems with verb forms. The students who attempted to use the past progressive, present perfect tense, past perfect tense and passive voice were totally incapable of using them correctly. After these tenses, articles was the area with the highest percentage of errors (75%). This was followed by plurality (67%), and simple past tense (53%), simple future tense (50%), simple present tense (26%), prepositions (20%) and subject-verb agreement (6%). The students demonstrated that they were competent in the use of pronouns as all their attempts were correct.